Electrical properties of AlNxOy thin films prepared by reactive magnetron sputtering - Borges, Joel Nuno Pinto (2012)
Direct current magnetron sputtering was used to produce AlNxOy thin films, using an aluminum target, argon and a mixture of N2+O2 (17:3) as reactive gases. The partial pressure of the reactive gas mixture was increased, maintaining the discharge current constant. Within the two identified regimes of the target (metallic and compound), four different tendencies for the deposition rate were found and a morphological evolution from columnar towards cauliflower-type, ending up as dense and featureless-type films. The structure was found to be Al-type (face centered cubic) and the structural characterization carried out by X-ray 2 diffraction and transmission electron microscopy suggested the formation of an aluminumbased polycrystalline phase dispersed in an amorphous aluminum oxide/nitride (or oxynitride) matrix. This type of structure, composition, morphology and grain size, were found to be strongly correlated with the electrical response of the films, which showed a gradual transition between metallic-like responses towards semiconducting and even insulating-type behaviors. A group of films with high aluminum content revealed a sharp decrease of the temperature coefficient of resistance (TCR) as the concentration ratio of non-metallic/aluminum atomic ratio increased. Another group of samples, where the non-metallic content became more important, revealed a smooth transition between positive and negative values of TCR. In order to test whether the oxynitride films have a unique behavior or simply a transition between the typical responses of aluminum and of those of the correspondent nitride and oxide, the electrical properties of the ternary oxynitride system were compared with AlNx and AlOy systems, prepared in similar conditions.